Relative efficacy and safety of topical non-steroidal anti-inflammatory drugs for osteoarthritis: a systematic review and network meta-analysis of randomised controlled trials and observational studies - Zeng, Chao (Br J Sports Med, 2018)
OBJECTIVES: To compare the efficacy and safety of topical non-steroidal anti-inflammatory drugs (NSAIDs), including salicylate, for the treatment of osteoarthritis (OA). METHODS: PubMed, Embase, Cochrane Library and Web of Science were searched from 1966 to January 2017. Randomised controlled trials (RCTs) comparing topical NSAIDs with placebo or each other in patients with OA and observational studies comparing topical NSAIDs with no treatment or each other irrespective of disease were included. Two investigators identified studies and independently extracted data. Bayesian network and conventional meta-analyses were conducted. The primary outcomes were pain relief for RCTs and risk of adverse effects (AEs) for observational studies. RESULTS: 43 studies, comprising 36 RCTs (7 900 patients with OA) and seven observational studies (218 074 participants), were included. Overall, topical NSAIDs were superior to placebo for relieving pain (standardised mean difference (SMD)=−0.30, 95% CI −0.40 to –0.20) and improving function (SMD=−0.35, 95% CI −0.45 to –0.24) in OA. Of all topical NSAIDs, diclofenac patches were most effective for OA pain (SMD=−0.81, 95% CI −1.12 to –0.52) and piroxicam was most effective for functional improvement (SMD=−1.04, 95% CI −1.60 to –0.48) compared with placebo. Although salicylate gel was associated with higher withdrawal rates due to AEs, the remaining topical NSAIDs were not associated with any increased local or systemic AEs. CONCLUSIONS: Topical NSAIDs were effective and safe for OA. Diclofenac patches may be the most effective topical NSAID for pain relief. No serious gastrointestinal and renal AEs were observed in trials or the general population. However, confirmation of the cardiovascular safety of topical NSAIDs still warrants further observational study.